MEDIATING ROLE OF UNEMPLOYMENT ANXIETY IN THE RELATIONSHIP BETWEEN GENERAL SELF-EFFICACY AND JOB SEARCHING COMPETENCE LEVEL - Özlem Karadağ Ak; Aslan Şendoğdu; Ayşe Elif Yazgan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The aim of the study is to measure the role of unemployment anxiety in the relationship between self-efficacy and job searching competence level of students who graduated from Necmettin Erbakan University, Faculty of Applied Sciences, Department of Finance and Banking between 2017 and 2020. The research population consists of 328 graduate students. SPSS package software was used during the phase of data analysis. It was determined that those with work experience had lower overall unemployment anxiety and a higher level of job search competence. A moderate negative relationship was found between general self-efficacy and general unemployment anxiety; a weak negative relationship was found between general unemployment anxiety and job search competence level; and a positive moderate relationship was found between general self-efficacy and job search competence level. In the light of the results obtained, it was seen that general self-efficacy increases the level of job search competence. In addition, general self-efficacy relieves general unemployment anxiety. General unemployment anxiety also negatively reduces the level of job search competence. In addition, based on the results of the Bootstrapp analysis, it was determined that the general unemployment concern had a partial mediating role in the relationship between general self-efficacy and job searching competence level.